2010
DOI: 10.1007/s12160-010-9204-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Suppression Tendencies as Predictors of Symptoms, Mood, and Coping Appraisals During AC Chemotherapy for Breast Cancer Treatment

Abstract: Tendencies to suppress negative emotions have been shown to predict adjustment to cancer and cancer progression. We examined whether emotional suppression, in terms of both general and emotion-specific tendencies, predict symptom reports, mood states, and coping appraisals during adriamycin/doxorubicin, cyclophosphamide/cytoxan chemotherapy for breast cancer. Forty participants completed a measure yielding scores for anxiety suppression, anger suppression, depression suppression, and total emotional suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 69 publications
3
39
1
2
Order By: Relevance
“…However, other studies found that emotion suppression or dampening (as measured by the CECS) was not significantly related to psychological distress, autonomic physiology, or survival Giese-Davis et al, 2008;Goodwin et al, 2004;Nakatani et al, 2014;Watson et al, 1999).Emotional dampening, as measured by the WCQ, was associated with longer survival times (Andreu et al, 2012;Classen et al, 1996;Reynolds et al, 2000;Schlatter et al, 2010;Tamagawa et al, 2013).…”
Section: Dimensions Of Emotional Regulation Found In the Included Stumentioning
confidence: 97%
See 1 more Smart Citation
“…However, other studies found that emotion suppression or dampening (as measured by the CECS) was not significantly related to psychological distress, autonomic physiology, or survival Giese-Davis et al, 2008;Goodwin et al, 2004;Nakatani et al, 2014;Watson et al, 1999).Emotional dampening, as measured by the WCQ, was associated with longer survival times (Andreu et al, 2012;Classen et al, 1996;Reynolds et al, 2000;Schlatter et al, 2010;Tamagawa et al, 2013).…”
Section: Dimensions Of Emotional Regulation Found In the Included Stumentioning
confidence: 97%
“…A majority of studies have used the CECS as an overall scale to measure "control of emotions" or "suppression of emotions". It has been the most common scale used to evaluate emotion control in the context of breast cancer and presented good internal consistency with α's ranging from .83 to .95 Andreu et al, 2012;Cameron et al, 2007;Classen et al, 1996;Giese-Davis et al, 2002, 2006bIwamistu et al, 2003Iwamistu et al, , 2005aIwamistu et al, , 2005bSchlatter et al, 2010) and reliability with 3-4 month testretest reliability = .95 . The CECS has been used with a wide variety of populations (see Table 1 for data on the number of publications describing the use of the CECS and all the measures reviewed) and has shown similar levels of reliability.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A diagnosis of breast cancer can be worrying (3) and is frequently associated with anxiety and depression (4), but breast cancer patients also experience psychological distress after surgery due to the psychological burden of longterm treatments (5) such as chemotherapy, radiotherapy and endocrine treatment. These therapies can have debilitating side effects (6)(7)(8)(9)(10)(11). Furthermore, patients undergoing treatments also experience psychological distress from a fear of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have confirmed that further to extreme anger, suppression, repression or restraint of anger are emotions generally exhibited by breast cancer patients [2]. Epidemiological studies have reported that participation in psychological support groups is associated with better health outcomes for these patients, calling for an integration of such a modality in cancer management and treatment [3].…”
Section: Introductionmentioning
confidence: 95%